Istirātijiyyatu Takwīn al-Bī’ah Li Da’mi Iktisābi al Mahārāt al-Lughawiyyah fi al-Ma’āhid al-Islamiyyah fī Jāwā al-Wusthā (Dirāsah al-Hālah fī Ma’hādi Alfirā al-Hadīts al-Islāmiy wa Ma’hadi al-Hidāyah al-Islāmiy wa Ma’hadi al-Ihsān al-Islāmy) - Ade Ruswatie; Imam Asrori; Syuhadak Sholeh (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2021)
This study aimed to investigate the strategies employed to establish a language environment that supports Arabic language acquisition at Elfira Islamic Modern Boarding School, Al Hidayah Islamic Boarding School, and Al Ikhsan Islamic Boarding School. A qualitative field research design was adopted to obtain an in-depth understanding of the language environment implemented in these institutions. Data were collected through interviews, observations, and documentation, and subsequently analyzed using qualitative data analysis procedures, including data reduction, data display, and conclusion drawing. The findings indicate that the three Islamic boarding schools implement a range of strategies to promote an effective Arabic language environment. These strategies include establishing dedicated language environments or language rooms, developing language-based student organizations, providing library resources that support language learning, designating specific days for the exclusive use of Arabic as the official language, displaying announcements in Arabic throughout the school environment, encouraging the use of Arabic during classroom instruction and group discussions, implementing disciplinary measures to reinforce language policies, and conducting regular evaluations to monitor students’ language development. The study concludes that the integration of these complementary strategies contributes to the creation of a supportive language environment that facilitates Arabic language acquisition and encourages students to use the target language consistently in both academic and daily communication.